The Influence of Modes of Deposition of Coatings on the Corrosion Resistance of Welded Joints of Steels in Acidic Media; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Saraev Yu. N. (2016, 2016)
Title screen